Roll‐Coated Fabrication of Fullerene‐Free Organic Solar Cells with Improved Stability. Issue 6 (28th April 2015) - Cheng, Pei; Bai, Huitao; Zawacka, Natalia K.; Andersen, Thomas R.; Liu, Wenqing; Bundgaard, Eva; Jørgensen, Mikkel; Chen, Hongzheng; Krebs, Frederik C.; Zhan, Xiaowei
<x xml:space="preserve">Abstract</x> Large area, fullerene‐free organic solar cells with improved stability and efficiency of up to 1% are fabricated by the roll‐coating process on indium tin oxide free and flexible substrates, under ambient conditions.